2006
DOI: 10.1002/jmri.20795
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between dynamic contrast‐enhanced magnetic resonance imaging–derived measures of tumor microvasculature and interstitial fluid pressure in patients with cervical cancer

Abstract: Purpose:To correlate permeability (rk trans ), extracellular volume fraction (rv e ), relative to muscle and initial area under the enhancement curve (IAUC 60m ) determined by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) with in vivo measurements of interstitial fluid pressure (IFP) in patients with cervical cancer. Materials and Methods: DCE-MRI and IFP measurementswere performed of cervical tumors of 32 patients prior to therapy. Median tumor rk trans and rv e were derived from a bidirectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…Treatment of neuroblastoma xenografts with bevacizumab increased the penetration of a chemotherapeutic drug for 1 to 3 days after drug treatment (46), and a similar observation was made in HT29 tumors (47). A reduction in IFP may explain the increase in AUC 600 observed here because a negative correlation has been observed between AUC and IFP in cervical cancer, thought to be due to high IFP resulting in increased resistance to tumor blood flow (48). The failure to detect increased pyruvate concentrations in the HT29 tumors following bevacizumab treatment (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Treatment of neuroblastoma xenografts with bevacizumab increased the penetration of a chemotherapeutic drug for 1 to 3 days after drug treatment (46), and a similar observation was made in HT29 tumors (47). A reduction in IFP may explain the increase in AUC 600 observed here because a negative correlation has been observed between AUC and IFP in cervical cancer, thought to be due to high IFP resulting in increased resistance to tumor blood flow (48). The failure to detect increased pyruvate concentrations in the HT29 tumors following bevacizumab treatment (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Because of no significant difference in tumour cell shape after treatment ( Figure 3A), intra-cellular volume did not change. Decreased apparent diffusion coefficient, therefore, reflected a decrease in Furthermore, similar to negative correlation between tumour interstitial fluid pressure and permeability of tumour (Haider et al, 2007), IAUGC, K trans , and v p showed a moderate negative correlation to apparent diffusion coefficient, suggesting that these parameters may be providing similar information. As apparent diffusion coefficient is acquired in clinic widely to detect and diagnose a tumour, it could apply conveniently to examine the permeability of tumour in patients.…”
Section: Discussionmentioning
confidence: 73%
“…Among those 7 centres that use IV contrast medium, 6 use a dynamic acquisition and 1 uses a semidynamic one. The results of the literature are also variable with some authors using IV contrast medium systematically in all cases [10][11][12] whereas other authors not using IV contrast medium at all [13,14]. In a dynamic acquisition, contrast enhancement of the tumour is lower than the myometrium in the early phase, whereas on the late phases, tumour signal intensity is higher than the myometrium.…”
Section: B Use Of Intravenous Contrast Mediummentioning
confidence: 99%